PELATIHAN PEMBUATAN LMS ONLINE BAGI GURU PAI SEBAGAI SARANA BELAJAR MANDIRI SISWA SMA DI KOTA PEKALONGAN - Dirasti Novianti; Alyan Fatwa; Mohammad Syaifuddin; Reza Hidayat (LP2M Universitas Ibrahimy, 2024)
The quality of mutual learning will be guaranteed if you keep up with changing times. In the current era, technology-related phenomena play a very important role in the field of education. Therefore, PAI high school teachers in the city of Pekalongn need to always update their technology mastery skills. The online learning management system based on the Google site aims to be an alternative technology that can be used in learning. The aim of this research is to hope that students can learn independently and teachers are more creative in developing teaching materials. Based on these considerations, the service team provided training on creating and using an online LMS to PAI teachers. The research method CBR (Community Based Research) is used in community service activities. Participants in this training are PAI teachers who are members of the MGMP PAI SMA Pekalongan City. As a result of this activity, PAI teachers were able to create and use an online LMS based on the Google site which was adapted to the open materials of each training participant. Suggestions for further service can optimize the LMS on a different basis.